Alright, to put it in standard form, you make it look like this:

Ax + By = C

Where A, B, and C are real numbers.

Let's look at the first one:

2x = -5y + 11

To put this in standard form all we do is add 5y to both sides:

2x + 5y = -5y + 11 + 5y

2x + 5y = 11

Ax + By = C

So it checks out.

Let's look at the second one:

4x - 7y + 15 = 0

To put this in standard form all we do is subtract 15 from both sides:

4x - 7y + 15 - 15 = 0 - 15

4x - 7y = -15

Which is the same as

4x + (-7)y = -15

Ax + By = C

So it checks out as well.

Let's look at the third one:

2x + 10 = 3y -1

To put this in standard form, we need to take two steps, first is to bring the y to the same side as the x by subtracting 3y from both sides:

2x + 10 - 3y = 3y - 1 - 3y

2x + 10 - 3y = -1

The second step is getting the 10 out of the side with the x and the y, so we subtract 10 from both sides:

2x + 10 - 3y - 10 = -1 - 10

2x - 3y = -11

Ax + By = C

So it checks out as well

2x + (-3)y = -11 is the same as 2x - 3y = -11 if you wanted to show that it still matches the standard form.

I hope this helps.